Pigeon Pea, An Emerging Source of Plant-Based Proteins - Locali-Pereira, Adilson Roberto [UNESP]; Boire, Adeline; Berton-Carabin, Claire; Taboga, Sebastião Roberto [UNESP]; Solé-Jamault, Véronique; Nicoletti, Vânia Regina [UNESP] (My University, 2023)
Making use of neglected pulse crops is a way to promote biodiversity and combat malnutrition in emerging countries, as well as a strategy to provide alternative and resilient sources of plant-based proteins. Pigeon pea (Cajanus cajan) is a pulse native to tropical and subtropical regions, such as Asia, India, and South America. Despite its great nutritional potential, pigeon pea is an underutilized crop, and its production is restricted to smallholder cultivators. Pigeon pea exploration for food application is a means to boost the cultivation and valorization of this crop, in addition to contributing to meeting the worldwide demand for high quality plant-based proteins obtained from sustainable crops. This review synthesizes the main research findings involving pigeon pea exploration for food applications, from the processing of its seeds and flours to the extraction and modification of its proteins, highlighting its potential as a food ingredient. Several initiatives have been carried out with the aim of investigating and improving the functional qualities of pigeon pea. Aqueous fractionation has been investigated under different conditions, showing it to be a viable process to produce protein-rich ingredients. Modifications of proteins, as in enzymatic hydrolysis processes, allow for releasing bioactive peptides of interest for applications in functional foods. Despite the overall potential, a knowledge gap has been identified regarding bulk rheological and interfacial properties of pigeon pea proteins, which need to be further investigated.
Keywords: alternative protein; antioxidant activity; Cajanus cajan; digestibility; protein extraction; pulse